Smallholder access to quality and diverse seed in Uganda: implications for food security - Otieno, G.; López Noriega, Isabel; Reynolds, Travis W. (2016)
This policy briefs presents smallholder farmers' preferences and major challenges when accessing seed in Uganda. It reflects on the weaknesses of the formal and informal seed production and distribution systems and presents some practical recommendations for putting in place alternative and integrative seed quality control systems that can help fill in the gaps that the formal and informal systems cannot address separately.